Stress intensification – an abnormal phenomenon observed during stress relaxation of dynamic coordination polymer - N. N. Xia; M. Z. Rong; M. Q. Zhang; S.-W. Kuo (eXPRESS Polymer Letters, 2016)
The authors report that during tensile stress relaxation test of a polyurethane crosslinked by catechol-iron coordination bonds, the stress gradually increases with time after the initial drop, which differs from the documented behaviors of other materials. Based on model experiment and structural characterization, water triggered rapid increase of dynamic crosslinkages accompanied by Poisson’s contraction is found to be responsible for the stress intensification effect. In addition, the influential factors are carefully discussed. The findings might help to develop novel polymeric materials with improved application performance under loading conditions.